Moral Perception and the Contents of Experience - Werner, Preston J. (2016)
I defend the thesis that at least some moral properties can be part of the contents of experience. I argue for this claim using a contrast argument, a type of argument commonly found in the literature on the philosophy of perception. I first appeal to psychological research on what I call emotionally empathetic dysfunctional individuals (eedis) to establish a phenomenal contrast between eedis and normal individuals in some moral situations. I then argue that the best explanation for this contrast, assuming non-skeptical moral realism, is that badness is represented in the normal individual’s experience but not in the eedi’s experience. I consider and reject four alternative explanations of the contrast.
Keywords: Moral Realism; Ethics; perception of higher-order properties; moral perception; moral epistemology; Metaethics